2016
DOI: 10.1139/apnm-2015-0541
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus helveticus Lafti L10 supplementation reduces respiratory infection duration in a cohort of elite athletes: a randomized, double-blind, placebo-controlled trial

Abstract: A randomized, double-blind, placebo-controlled study was conducted to evaluate if Lactobacillus helveticus Lafti L10 (Lallemand Health Solutions, Montreal, Que., Canada) supplementation during 14 weeks in winter can influence the duration, severity, and incidence of upper respiratory tract illness (URTI), as well as to monitor different immune parameters in the population of elite athletes. Before and after the treatment, cardiopulmonary testing and self-rated state of moods evaluation (by Profile of Mood Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 30 publications
2
86
0
Order By: Relevance
“…Haywood et al (2014) conducted an interesting study with probiotic in Rugby players with a higher dose multi-species probiotic (4 weeks) 11 . All the subjects in placebo group reported URS higher than probiotic group, the duration and severity of the URS episodes and symptoms was not different between groups, but the number of illness days in placebo groups was a trend to be higher when compared to treatment 11 Specific probiotics strains attenuate URS 17,18,22 , however the data with non-athlete subjects is quite small. And no alterations in cellular activity were found to explain the reduction of the URS found in the probiotic group 22 .…”
Section: Accepted Manuscriptmentioning
confidence: 91%
See 1 more Smart Citation
“…Haywood et al (2014) conducted an interesting study with probiotic in Rugby players with a higher dose multi-species probiotic (4 weeks) 11 . All the subjects in placebo group reported URS higher than probiotic group, the duration and severity of the URS episodes and symptoms was not different between groups, but the number of illness days in placebo groups was a trend to be higher when compared to treatment 11 Specific probiotics strains attenuate URS 17,18,22 , however the data with non-athlete subjects is quite small. And no alterations in cellular activity were found to explain the reduction of the URS found in the probiotic group 22 .…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…In a study by Gill et al (2016) with short term high dose probiotic utilization (L. Casei 1x10 11 per 7 th days) the probiotic group did not demonstrate alterations in systemic cytokine profile or gut permeability compared to placebo 10 . Majority of studies that showed positive effects employed long periods of probiotics apply 7,14,15,[18][19][20][21][22]25 .…”
Section: C E P T E D M a N U S C R I P Tmentioning
confidence: 99%
“…Probiotics are live organisms that when consumed, impose a wide array of beneficial physiological effects on humans, most notably promoting improved gut microbiota [ 14 ]. These microorganisms have been shown to exert immunomodulatory effects [ 15 ] by decreasing pro-inflammatory cytokines in circulation [ 16 ] and supporting mucosal defense [ 17 , 18 ]. In athletes, probiotics have been reported to reduce the number, duration, and severity of infections [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pyne et al (2015) have provided an excellent summary of 15 clinical trials through 2014 in which 10 of 13 studies reported favorable changes in immune and inflammatory markers, and six of seven studies reporting clinical outcomes for URTI report decreased incidence, duration, and or severity with probiotic supplementation. Trials published more recently follow a similar pattern with decreased (∼half) incidence, duration (∼2 days shorter), and severity (fewer symptoms) of URTI (Michalickova et al, 2016;Strasser et al, 2016). An additional trial was unable to distinguish placebo and probiotic treatments because of unexpectedly low incidence of URTI in both groups (Gleeson et al, 2016).…”
Section: Probioticsmentioning
confidence: 62%